Harold Rugg’s Social Studies in Alberta - von Heyking, Amy (Alberta Journal of Educational Research, 2023)
This historical inquiry analyzes the appeal of Harold Rugg’s social reconstructionist social studies for Alberta educators in the 1930s. It demonstrates why and how this small, rural province adapted Rugg’s curriculum, a program and resources he developed to guide American students’ understanding of what he called “the American problem.” It identifies key elements of Rugg’s program, including its philosophical orientation and its practical teaching resources that were particularly appealing to educational leaders. The inquiry identifies legacies of the origins of the program for the provincial social studies curriculum. Keywords: Social studies, Harold Rugg, social reconstructionism, curriculum reform, Alberta Cette enquête historique analyse l'attrait des études sociales reconstructionnistes de Harold Rugg pour les éducateurs de l'Alberta dans les années 1930. Elle démontre pourquoi et comment cette petite province rurale a adapté le curriculum de Rugg, un programme et des ressources qu'il a développés pour aider les élèves américains à comprendre ce qu'il appelait "le problème américain". Elle identifie les éléments clés du programme de Rugg, notamment son orientation philosophique et ses ressources pédagogiques pratiques qui attiraient particulièrement les leadeurs en éducation. L'enquête identifie les retombées des origines du programme sur le programme provincial d'études sociales. Mots clés : études sociales, Harold Rugg, reconstruction sociale, réfonte du curriculum, Alberta